Stratigraphic description (peat and gyttja type) of exemplary cores from 49 peatlands in Lower Lusatia, Germany, sampled in 2012 - Caroline Greiser; Hans Joosten (PANGAEA, 2018)
The datasets contain detailed description of the stratigraphy of 49 drilling cores, taken from 49 peatlands in Lower Lusatia, Germany in year 2012. Cores were taken at the peatlands deepest point. Descriptions include peat and gyttja types in each distinct layer including degree of decomposition and any other macrofossil/charcoal that could be identified in field (e.g. Nymphaea seeds).
Supplement to: Greiser, C; Joosten, H (2018): Archive value: measuring the palaeo-information content of peatlands in a conservation and compensation perspective. International Journal of Biodiversity Science, Ecosystems Services and Management, 14(1), 209-220, https://doi.org/10.1080/21513732.2018.1523229